2022
DOI: 10.1038/s41598-022-21850-9
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human adipose-derived stem cells overexpressing LIF/IFN-β promotes recovery in experimental autoimmune encephalomyelitis (EAE)

Abstract: Multiple Sclerosis (MS) is the most common demyelinating disease with inflammatory demyelination in the central nerve system. Besides the defect in the myelin repair process, the balance change in inflammatory and anti- inflammatory cytokines is one of the most significant factors in MS pathogenesis. This study aimed at evaluating the effects of co-overexpressing beta interferon (IFN-β) and Leukemia inhibitory factor (LIF) in human adipose-derived stem cells (IFN-β/LIF-hADSCs) on the experimental autoimmune en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The role of ASCs in EAE has been indirectly proven by their beneficial therapeutic effects, since administration of healthy ASCs has been shown to delay the disease onset and reduce disease severity by inhibiting immune cell proliferation [162]. Supporting these results, Yousefi et al demonstrated that transplantation of ASC-overexpressing leukemia inhibitory factor (LIF), a neurotropic agent, and IFNβ, an anti-inflammatory cytokine, promoted the recovery from EAE due to (i) increased immunomodulatory effects, (ii) reduction of the extent of demyelination, (iii) enhancement of the number of oligodendrocytes, and (iv) increase of the amount of MBP protein and further myelin production [163]. However, the anthropometric status of ASC donors appears of particular importance, since transplantation of ASCs from obese donors exacerbated EAE disease by increasing the expression of pro-inflammatory cytokines and inducing proliferation and differentiation of CD4 and CD8+ T cells.…”
Section: Contribution Of Ascs and Mscsmentioning
confidence: 92%
“…The role of ASCs in EAE has been indirectly proven by their beneficial therapeutic effects, since administration of healthy ASCs has been shown to delay the disease onset and reduce disease severity by inhibiting immune cell proliferation [162]. Supporting these results, Yousefi et al demonstrated that transplantation of ASC-overexpressing leukemia inhibitory factor (LIF), a neurotropic agent, and IFNβ, an anti-inflammatory cytokine, promoted the recovery from EAE due to (i) increased immunomodulatory effects, (ii) reduction of the extent of demyelination, (iii) enhancement of the number of oligodendrocytes, and (iv) increase of the amount of MBP protein and further myelin production [163]. However, the anthropometric status of ASC donors appears of particular importance, since transplantation of ASCs from obese donors exacerbated EAE disease by increasing the expression of pro-inflammatory cytokines and inducing proliferation and differentiation of CD4 and CD8+ T cells.…”
Section: Contribution Of Ascs and Mscsmentioning
confidence: 92%
“…More recent studies on EAE mice, following intravenous administration of hAT-MSCs overexpressing IFN-b/LIF, reported a reduction in demyelination, an increase in the number of Olig2+ cells, and an elevation in the myelin basic protein (MBP) expression. This can, in turn, increase the production of myelin (Yousefi et al, 2022).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Critically, stem cells exhibit immunomodulatory effects that attenuate inflammatory processes, offering a novel approach to mitigating the progression of MS lesions ( 5 ). Empirical studies, including laboratory and animal model research, have demonstrated the therapeutic efficacy of hematopoietic, neural, and embryonic stem cells, indicating substantial therapeutic promise ( 6 , 7 ). Preliminary clinical trials have corroborated these findings, signaling a promising horizon for individuals afflicted with MS ( 8 ).…”
Section: Introductionmentioning
confidence: 99%